Pemberian Inokulum yang Terseleksi pada Proses Fermentasi Kakao untuk Memperbaiki Mutu dan Kualitas Kakao di Sulawesi Tengah - Alwi Muhammad (Biocelebes, 2008)
Microbe exploiting for the ferment of agricultural produce in the form of seed cocoa have been done.This research use two pure type isolate and one mixture culture. Pure Isolate in the form of Acetobacter aceti (group of bacteria) and Hansenula anomala (group khamir) while mixture culture in the form of mixture both. This research use the seed cocoa which is taken away from Sulawesi Tengah area and executed at March - October 2007 in Biology Laboratory of FMIPA Untad. Result of research obtained by that pure use isolate do not have an effect on the reality to parameter tested, but use of mixture culture of between A. aceti and H. anomala give the real influence to tested parameter, oldly is best ferment that is 4 day. Key words : Fermentation, Cocoa, Acetobacter, Hansenula